Longitudinal Cognitive Outcomes in Children With HIV in Zambia: 2-Year Outcomes From the HIV-Associated Neurocognitive Disorders in Zambia (HANDZ) Study. (1st October 2022) - Patil, Gauri; Mbewe, Esau G.; Kabundula, Pelekelo P.; Smith, Hannah; Mwanza-Kabaghe, Sylvia; Buda, Alexandra; Adams, Heather R.; Potchen, Michael J.; Mweemba, Milimo; Johnson, Brent A.; Schifitto, Giovanni; Gelbard, Handy; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: To describe longitudinal outcomes and predictors of cognitive outcomes in children with HIV in Zambia. Background: Multiple studies have shown that children with HIV are at risk for impaired cognition. However, there are limited data on longitudinal cognitive outcomes in children with HIV. Methods: We conducted a prospective cohort study of 208 perinatally infected children with HIV ages 8–17 years, all treated with antiretroviral therapy, and 208 HIV-exposed uninfected controls. Participants were followed for 2 years. Cognition was assessed with a custom NIH Toolbox Cognition Battery, and tests were combined to generate a Summary Cognition Score (SCS). The contribution of potential risk factors to outcomes was explored using regression models and group-based trajectory modeling. Results: HIV was strongly associated with lower SCS at baseline [β-14, 95% confidence interval (CI): −20 to −7, P < 0.001]. Change scores over time were similar between groups, but poorer average performance in children with HIV persisted at the 2-year follow-up visit (adjusted β = −11, 95% CI: −22 to −0.3, P = 0.04). Other than HIV, the strongest predictors of baseline SCS included socioeconomic status index (β =3, 95% CI: 1, 5, P = 0.004), history of growth stunting (β=−14, 95% CI: −23 to −6, P = 0.001), history of CD4 count below 200 (β = −19, 95% CI: −35 to −2, P = 0.02), and history of World Health Organization stage 4 disease (β = −10, 95% CI: −19 to −0.2, P = 0.04). In the group-based trajectory model, HIV+ status predicted membership in the lowest performing trajectory group (odds ratio 2.5, 95% CI: 1.2 to 5.1, P = 0.01). Conclusions: Children with HIV are at risk of poor cognitive outcomes, despite chronic treatment with antiretroviral therapy.